Petrological Characteristics and Rock Nomenclature of Sedimentary Bauxite Gas Reservoir: A Case Study of Bauxite in Taiyuan Formation of Ordos Basin - Na Liu; Junxiang Nan; Xingying Wang; Yanning Yang; Peng Yin; Renyan Zhang (Geofluids, 2023)
With the great breakthrough in natural gas exploration of Paleozoic Taiyuan formation in Longdong exploratory area in the southwestern part of Ordos Basin, it is urgent to solve the petrological nomenclature of sedimentary bauxite, so as to further study the pore formation mechanism, distribution law, and controlling factors of bauxite reservoirs. In this paper, X-ray diffraction, polarizing microscope, scanning electron microscope, and other methods are used to analyze the mineral composition and structure of bauxite rocks in the study area and give appropriate names. The results show that the sedimentary sequence of bauxite in the study area can be divided into five sections: A, B, C, D, and E. The main mineral components are diaspore (C section content can be more than 90%), illite, kaolinite, and chlorite; accessory mineral include anatase and pyrite; trace components include quartz, feldspar, rutile, hematite, and rock salt; and some of the pores are filled with calcite, siderite, and (iron) dolomite. The rock structure is mainly bedding and massive structure, and some of them have geopetal structure. The texture mainly consists of granular texture, grain (powder crystal) texture, gel texture, and algal bonding texture. Considering the special lithology of section A~C and the lack of existing nomenclature method, based on mineral composition and sedimentary fabric, a triangulation classification nomenclature method is established, which adopts structure+texture as secondary name and the main mineral components diaspore-mud-pyrite of the three end-member mineral components as primary name. It can not only highlight the mineral assemblage characteristics of sedimentary sequence of bauxite but also reflect the lithologic characteristics of reservoir development section and the influencing factors of reservoir formation, effectively reflecting the petrological characteristics of bauxite reservoir. Among them, the diaspore rocks with granular, bean-oolitic, and grain texture are the main lithologies forming the natural gas reservoir space of Taiyuan formation in Longdong area. The naming method is feasible and reliable for sedimentary bauxite rocks, which lays a good foundation for the study of natural gas reservoir, pore formation mechanism, and distribution law in Longdong area, southwest of the basin.